Gyrokinetic Particle Simulation of Compressional Electromagnetic Modes (Communications in Computational Physics, 2008)
A gyrokinetic particle simulation model is developed for simulations of the compressional electromagnetic turbulence driven by the mirror instability. Results of the linear simulations of mirror modes agree well with the analytic dispersion relation. Nonlinear simulations of a single mode find that the mirror instability saturates via a phase-space trapping due to the nonlinear wave-particle interaction when the instability drive is weak.